Extracorporeal Membrane Oxygenation as a Bridge to Chemotherapy in an Orthodox Jewish Patient. (5th August 2014) - Meltzer, Ellen C.; Ivascu, Natalia S.; Acres, Cathleen A.; Stark, Meredith; Furman, Richard R.; Fins, Joseph J.
Abstract: Objective: Venoarterial extracorporeal membrane oxygenation (VA-ECMO) for cardiopulmonary support offers survival possibilities to patients who otherwise would succumb to cardiac failure. Often referred to as "a bridge to recovery, " involving a ventricular assist device or cardiac transplantation, this technology only affords temporary cardiopulmonary support. Physicians may have concerns about initiating VA-ECMO in patients who, in the absence of recovery or transfer to longer-term therapies, might assert religious or cultural objections to the terminal discontinuation of life-sustaining therapy (LST). We present a novel case of VA-ECMO use in an Orthodox Jewish woman with potentially curable lymphoma encasing her heart to demonstrate the value of anticipating and preemptively resolving foreseeable disputes. Patient: A 40-year-old Hasidic Orthodox Jewish woman with lymphoma encasing her right and left ventricles decompensated from heart failure before chemotherapy induction. The medical team, at an academic medical center in New York City, proposed VA-ECMO as a means for providing cardiopulmonary support to enable receipt of chemotherapy. Owing to the patient's religious tradition, which customarily prohibits terminal discontinuation of LST, clinical staff asked for an ethics consultation to plan for initiation and discontinuation of VA-ECMO. Interventions: Meetings were held with the treating clinicians, clinical ethics consultants, family, religious leaders, and cultural liaisons. Through a deliberative process, VA-ECMO was reconceptualized as a bridge to treatment and not as an LST, a designation assigned to the chemotherapy on this occasion, given the mortal threat posed by the encasing tumor. Conclusion: Traditional religious objections to the terminal discontinuation of LST need not preclude initiation of VA-ECMO. The potential for disputes should be anticipated and steps taken to preemptively address such conflicts. The reconceptualization of VA-ECMO as a bridge to treatment, rather than as an LST, can allow patients with objections to the terminal discontinuation of LST to receive interventions, such as chemotherapy, that might otherwise be precluded by critical physiology. Abstract : Venoarterial extracorporeal membrane oxygenation (VA-ECMO) for cardiopulmonary support offers survival possibilities to patients who otherwise would succumb to cardiac failure. The authors present a novel case of VA-ECMO use in an Orthodox Jewish woman with potentially curable lymphoma encasing her heart to demonstrate the value of anticipating and preemptively resolving foreseeable religious or cultural objections to the terminal discontinuation of life-sustaining therapy.